Dimensional Analysis With Case Studies in Mechanics - Tan, Qing-Ming.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Dimensional analysis is an essential scientific method and a powerful tool for solving problems in physics and engineering. This book starts by introducing the Pi Theorem, which is the theoretical foundation of dimensional analysis. It also provides ample and detailed examples of how dimensional analysis is applied to solving problems in various branches of mechanics. The book covers the extensive findings on explosion mechanics and impact dynamics contributed by the author$1 (Bs research group over the past forty years at the Chinese Academy of Sciences. The book is intended for advanced undergraduates and graduate students of physics and engineering, as well as research scientists and engineers working in related fields. Qingming Tan is a former researcher at the Institute of Mechanics, the Chinese Academy of Sciences, China.s
Introduction -- Fundamental Principles of Dimensional Analysis -- Problems in Fluid Mechanics -- Problems in Solid Mechanics -- Heat Conduction and Thermal Stress in Solids -- Problems of Coupling Fluid Motion and Solid Deformation -- Hydro-elasto-plastic Modeling -- Similarity Laws for Explosions -- Similarity Laws for High Velocity Impacts -- Normalization in Mathematical Simulations.
Keywords: Engineering; Functional analysis; Mechanics, applied; Civil engineering; Hydraulic engineering; Engineering; Theoretical and Applied Mechanics; Classical Continuum Physics; Functional Analysis; Civil Engineering; Geoengineering, Foundations, Hydraulics